Online knowledge construction in networked learning communities - Lee, Lai Har Judy; Rahmat, Rozi Binte; Lim, Poh Heng; Lin, Li; Tan, Toh Hwee (Proceedings of the International Conference on Networked Learning, 2018)
Networked Learning Communities (NLCs) comprise individuals from different schools or organisations collaborating with one another in purposeful and sustained professional development (Jackson & Temperley, 2007). Knowledge construction is central to the work of NLCs as networked learning entails the construction of new knowledge by tapping members’ personal practitioner knowledge and the public knowledge base. In Singapore, some NLCs sustain their professional learning through online interactions in collaboration groups within "One Portal All Learners (OPAL)", a learning and content management system developed by the Ministry of Education (MOE). This paper outlines a project that studied knowledge construction within 10 OPAL collaboration groups created by NLCs (“ONLCs”), the roles adopted by the members, and the factors that influenced members' participation in knowledge construction within the ONLCs. According to the Interaction Analysis Model (IAM) by Gunawardena, Lowe, and Anderson (1997), knowledge construction in online collaborative environments progresses over five levels: (a) sharing and comparing of information; (b) discovery and exploration of dissonance or inconsistency among ideas; (c) negotiation of meaning; (d) testing and modification; and (e) application of newly-constructed meaning. Findings revealed that the majority of the online knowledge constructions were at the level of sharing and comparing of information. Six possible factors that influenced members' engagement in knowledge construction in the ONLCs were identified through focus group discussions. The factors identified were (a) a structured approach for enacting NLCs, (b) organisational support, (c) a conducive environment that enables trust to be built among members, (d) shared ownership among members, (e) a culture of sharing that prioritises higher levels of knowledge construction, and (f) OPAL as an enabler. Using findings from the study and from literature, an implementation framework was developed to promote knowledge construction in ONLCs. The implementation framework was field-tested by four NLCs and then refined based on feedback gathered. The feedback gathered on the implementation framework was generally positive and participants found it to be comprehensive, although many felt that the efficacy of the implementation framework to support online knowledge construction may be limited by the affordances of the online collaborative workspace being used. However, the key to raising the level of knowledge construction could lie in nurturing a conducive environment and a culture of sharing, and fostering shared ownership. These three factors can work together to shape the dynamics within the NLC, to help members recognise the importance of co-owning and co-leading the NLC's professional learning.